PERAMALAN TINGKAT PRODUKSI TANAMAN PANGAN DAN TANAMAN PERKEBUNAN RAKYAT KABUPATEN BULUKUMBA MENGGUNAKAN METODE EXPONENTIAL SMOOTHING - Sauddin, Adnan; Nurman, Try Azisah; Wahyuni, Risa (Universitas Islam Negeri Alauddin Makassar, 2018)
In This article discusses about forcasting of agricultural production using expontential smoothing in time series analysis. In the sector of agriculture there are some kinds of food plantation and society plantation. Exponential smoothing is one of the method which can be used to predict the number of production which will come, the kinds of double exponential smoothing with alpha=1 and bheta=0.036 can be applied t the production data of the society agriculture and single exponential smoothing with alpha = 0.75 can be applied is society platation. The aim of the research is to know the production of the food plantation in 2020 and the the production of society plantation 2018 in Bulukumba regency. As a result of this research, it could be seen that the production of food plantation in 2020 the amount of 518.087,09 ton, and the production of plantation in 2018 in the amount of 43.814,05 ton